Pressure-induced softening of locust bean gum hydrogels: A counterintuitive alternative to freeze–thaw stiffening - Wenbo Fu; Pu Qiao; Henghui Bai; Kaiyuan Shi; Xingbang Dong; Jiaqing Zhang; Zhaoxu Du; Jun Kong; Haotian Yang; Xin Zhang; Ke Zhang; Lei Su; et al. (Proceedings of the National Academy of Sciences, 2026)
Hydrogels have been widely used in biomedical and environmental applications, yet precise control of mechanical properties (quantified by elastic modulus, G′) over a broad range remains essential for expanding their functionality. While pressure treatment typically enhances hydrogel strength through pressure-induced crosslinking, we report a counterintuitive phenomenon in locust bean gum (LBG) hydrogels: High-pressure processing induces softening rather than stiffening. Under repeated compression-decompression cycles up to 1.2 GPa, LBG hydrogels undergo progressive softening, with elastic modulus decreasing to approximately 31% of the initial value. Conversely, repeated freeze–thaw cycles enhance the modulus by approximately 2.3-fold. Scanning electron microscopy reveals a structural transition from a porous network to a flocculent morphology, corresponding to substantial alterations in elastic modulus and viscoelastic behavior. Mechanistic analysis suggests that pressure-induced disruption of hydrogen bonding, water redistribution, and structural rearrangement drive these changes. These findings demonstrate that pressure modulation can serve as a complementary method to conventional freeze–thaw treatment, offering precise control over hydrogel mechanical properties across a wide range.